Impaired STAT3-Dependent Upregulation of IL2Rα in B Cells of a Patient With a STAT1 Gain-of-Function Mutation - van Zelm, Menno C.; Bosco, Julian J.; Aui, Pei M.; De Jong, Samuel; Hore-Lacy, Fiona; O'Hehir, Robyn E.; Stirling, Robert G.; Cameron, Paul U. (Frontiers in Immunology, 2019)
Heterozygous STAT1 gain-of-function (GOF) mutations form the most common genetic cause of chronic mucocutaneous candidiasis (CMC). In such patients, increased STAT1 function leads to impaired STAT3-dependent activation of IL-17A and IL-17F in T cells, thereby causing impaired Th17 responses to Candida. In spite of the critical role of STAT3 in IL-21 signaling in B cells, nearly all STAT1 GOF patients have normal or high serum IgG. We here present a 44-year-old male with childhood onset of CMC and antibody deficiency since early adulthood. Sequence analysis of STAT1 revealed a heterozygous missense mutation in the coiled-coil domain (p.D168E), which resulted in increased STAT1 phosphorylation of B-cells activated with IFNα and IFNγ. IL-21 induced STAT3 phosphorylation and nuclear localisation were normal, but resulted in impaired upregulation of IL2Rα. This newly identified B-cell intrinsic impairment of STAT3 function could underlie the progressive development of hypogammaglobulinemia. Considering the high risk of bronchiectasis and irreversible organ damage, this case illustrates the need for monitoring of IgG levels and/or function in adult patients with STAT1 GOF mutations.